Stabilisation of heavy metals in soil using nanoscale zero-valent iron coated with palygorskite. Issue 3 (16th March 2021) - Mi, Xuan; Ren, Jun; Tao, Ling
ABSTRACT: The nanoscale zero-valent iron (nZVI) coated with palygorskite (PAL) was synthesised and used to remediate the soil contaminated by heavy metals. X-ray diffraction (XRD) and scanning electron microscopy (SEM) indicated that a large number of nanoscale particles (had a grain size of 40–60 nm approximately) were distributed on the surface or pores of PAL homogeneously. The CaCl2 extraction and TCLP test were carried out to evaluate the bioavailability and mobility of four metals in soil amended by PAL-nZVI. The loading mass ratio of 2:1 between PAL and nZVI showed the optimised effect during the heavy metals' stabilisation. BCR sequential extraction was employed to measure the change of metal fractions in soil. The residual fraction concentration increased significantly, indicating that the fraction of heavy metals tended to stabilise after amended with PAL-nZVI. The result of pot experience showed that the corn's biomass increased, and the uptake of heavy metals was reduced significantly, which suggested the PAL-nZVI could stimulate the growth of corn by increasing the stabilisation of heavy metals in soil. Thus, PAL-nZVI as a novel and high-efficiency amendment could be applied to remediate the heavy metals-contaminated soil.